THE PROBLEM WITH SUICIDAL BEHAVIOUR! - Bhana, Arvin (PINS-Psychology in Society, 2025)
Schlebusch, L (2005) Suicidal behaviour in South Africa. Pietermaritzburg: University of KwaZulu-Natal Press. ISBN 1-86914-077-X pbk. Pages xv + 233. At the outset, it has to be acknowledged that this was a difficult book to review. The book represents a practitioner / researcher perspective with the content supported by some empirical evidence as well as anecdotal or case study material. The difficulty lies essentially in the fact that the various chapters have been assembled employing varying levels of scientific academic writing and reporting. Given that the study of suicidal behaviour is burdened with methodological and design issues, the book details rates of suicide without apparently accounting for these methodological variations and which would tend to make some of them non-comparable. Sometimes, media reports are used to bolster the findings of a research study; at other times, it represents a case history of a particular type and form of suicidal behaviour. The research studies in themselves vary in their sophistication and the real difficulty is to know what to make of the evidence since there is little or no comment about critical research sample and design issues. A substantial part of the content is drawn from conference proceedings that the author has hosted. It is unclear if the conference proceedings represent an independent peer-review process.